Effective conductivity and permittivity of unsaturated porous materials in the frequency range 1 mHz–1GHz. Issue 1 (24th January 2013) - Revil, A.
Key Points A new model for the effective conductivity and permittivity It explains an important number of data in a broad frequency range It accounts for clay content, mineralogy and saturation